Assessment and management of scalds and burns in children. - Hollywood, Eleanor; O'Neill, Tracey (My University, 2014)
In childhood, burn or scald injuries are comparatively common, and the greatest risk is to infants and toddlers. The extent and severity of injuries can vary greatly, which can significantly affect recovery and outcome. To provide high quality nursing care to the child who has sustained a burn injury and the family, the children’s nurse should understand the pathophysiology of the trauma and the associated physical and psychological suffering. Evidence-based nursing management of these aspects is an essential component of recovery. Children’s nurses working in hospitals, schools or in the community can engage with parents, families, school staff and children to provide information, advice, and health and safety promotion for burn prevention.
PUBLISHED
Keywords: Accidents and emergencies; Accident prevention; Burns; Children; Accidents; Child nursing care; First aid